(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Since the situation of Covid-19 began, many prevention methods have been introduced to prevent the spread of the disease such as social distancing, avoid traveling to crowded areas and refrain from social activities as a result, the customer learns and adapts to the change of the new normal lifestyle. A trading logistics model has been changed from traditional commerce to E-commerce model. Meanwhile, some customers still passion for traditional commerce logistics model. Therefore, this research aims to study the customer behaviors and opinions that decide to go to the shopping center after the outbreak of the Covid-19. The research is done by using a questionnaire as a tool to collect the data. The statistical tools that use in the research are a percentage, mean, standard deviation, one-way analysis of variance test and Chi-square test. To answer the first hypothesis testing, one-way analysis of variance test is used and found that the differentiation of age, education level, occupation, income and region of residence lead to the customer opinion significantly different at the 0.05 level. For the second hypothesis testing, Chi-square is used and found that the differentiation of age, education level, occupation, income and region of residence lead to the customer behavior significantly different at the 0.05 level. Approximate distance when travel to the shopping center is less than 10 km. Finally, calculate a proportion of products that customer purchases from shopping center is a perishable product, the product that needs to be touched, requested After-sale service and Ready to bring the product home.